Analisis Kesalahan Dalam Menyelesaikan Soal Persamaan Kuadrat Pada Siswa Kelas IX SMP Negeri 1 Loura - Mone, Ariyanti; Lede, Yulius Keremata; Making, Samuel Rex Mulyadi (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to describe students' errors in solving quadratic equation problems. The subjects of the study were grade IX B students of SMP Negeri 1 Loura with a total of 13 students. The type of research used is descriptive qualitative using research instruments, test sheets and interviews. The tests used are quadratic equation material questions, while the type of interview conducted is in the form of semi-structured interviews. The results showed that reading error was 0.0%, problem misunderstanding error was 40%, problem transformation error was 60%, process skill error was 75%, final answer writing error was 20%. Student errors are caused by several things including: lack of understanding of the concept of quadratic equations, not focusing and not being careful in doing problems.